Metode Penyampaian dalam Pendidikan Islam - Jumrianah (ISEDU : Islamic Education Journal, 2025)
This study aims to explore the methods used in delivering Islamic Education to ensure that the material contained in the curriculum is effectively and efficiently understood by students. This research employs a qualitative library research approach, with sources including books, encyclopedias, scholarly journals, newspapers, magazines, and relevant documents. The study involves searching, collecting, organizing, and interpreting literature-based data to analyze educational delivery methods. The foundation of Islamic education delivery methods is rooted in religious, biological, psychological, and sociological considerations. Therefore, educators must apply appropriate teaching methods by taking into account students’ holistic development. Various traditional and contemporary methods are still in use, such as the exemplary method, reward and punishment, lecture, question and answer, discussion, storytelling, assignment, demonstration, as well as classical methods like bandongan, sorogan, and muzakarah. These methods continue to be relevant and effective in achieving the goals of Islamic education both in formal and non-formal learning environments.